How to Improve Farmers’ Green Production Level in a Targeted Manner? - Yu, YanLi; Lu, Ting; Hu, Ya Guan; Meng, KaiWen; Li, Hua (Frontiers in Environmental Science, 2022)
Improving farmers’ green production behavior can guarantee food safety at the source. In recent years, a rising number of studies have focused on food safety management and have provided general regulation recommendations. Unlike many studies, this study aimed to find targeted policy recommendations according to different spatial aggregations of non-green production behavior. In the current study, more than 800 tea farmers located in the Qinba and Huangshan Mountain regions of China were investigated. An order logit model was employed to evaluate the impact of government regulation and community governance on ignorant or unkind non-green tea production behavior. Furthermore, a multi-valued treatment effect model was also recruited to demonstrate the average treatment effect of government regulation and community governance. The results show that the difference in farmers’ ignorant or unkind non-green production behavior between regions is substantial but is similar in the same region. Farmers’ non-green production behavior is negatively impacted by community governance but not significantly affected by government regulation. Government regulation can effectively inhibit the occurrence of farmers’ unkind behavior, while community governance can effectively cause farmers’ unkind behavior. Thus, some measures to reduce local farmers’ non-green production behavior should be put forward according to the differences in the spatial distribution of non-green production behavior and the differences in the effect of government regulation and community governance.